Locally Taboo Words Within East Java Society: A Sociolinguistic Study - Br. Perangin-angin, Alemina; A. Jalil, Zurriyati; Pranata, Juli Samuel; Amalia, Firdha (International Journal of Culture and Art Studies, 2024)
Researchers can learn a lot about a culture's values, beliefs, and fears by looking at the things that people don't do. What a culture thinks is holy, dangerous, or rude can be shown by taboos. This can help us figure out how societies work and how they've changed over time. This article analyzes the use of taboos in the daily communication of the people of East Java, particularly adolescents. Rural and urban Javanese have differing perspectives on the usage of taboo language, respectively. This study intends to examine the opposition of views between rural and urban Javanese individuals who use taboo language to communicate, as well as the types of taboo words typically employed by Javanese people. The type of data obtained from the study is qualitative, thus the data that will be reported in this study will be in the context of the usage of taboo language by rural, urban, and East Java Province-dwelling Javanese. The data was also collected by Interviews: Talking to people from a wide range of backgrounds in depth. Ask them open-ended questions about how they feel about banned words when they're used, and how they make them feel. Since rural Javanese continue to use language and manners, their perspectives on taboo language analysis differ from those in urban areas. The East Javanese believe that profanity and restricted language should not be utilized in speech and social interactions.Â